Noticed d'Economie Politique (Quarterly Journal of Economics, 1887)
Noticed d'Économie Politique Get access The Quarterly Journal of Economics, Volume 1, Issue 3, April 1887, Page 356, https://doi.org/10.1093/qje/1.3.356 Published: 01 April 1887